The quest for continuous quality improvement in Australian long day care services: getting the most out of the Assessment and Rating process - Irvine, Susan Lee; Barblett, Lennie; Waniganayake, Manjula; Hadley, Fay; Andrews, Rebecca; Hatzigianni, Maria; Li, Hui; Lavina, Leanne; Harrison, Linda J.; Davis, Belinda (Frontiers in Education, 2024)
The National Quality Framework (NQF) was intended to drive continuous improvement in education and care services in Australia. Ten years into implementation, the effectiveness of the NQF is demonstrated by steady improvements in quality as measured against the National Quality Standard (NQS). The process of assessing and rating services is a key element in the NQF, drawing together regulatory compliance and quality assurance. This paper draws on findings from a national Quality Improvement Research Project investigating the characteristics, processes, challenges and enablers of quality improvement in long day care services, concentrating on Quality Area 1 Educational program and practice and Quality Area 7 Governance and Leadership. This was a mixed-method study focusing on long day care services that had improved their rating from Working Towards NQS to Meeting NQS or to Exceeding NQS. The study comprised three phases, and in this paper, we draw on Phase 3 to understand the contribution of the NQS Assessment and Rating (A&R) process to continuous quality improvement from the standpoint of providers and professionals delivering these services. Phase 3 involved qualitative case studies of 15 long day care services to investigate factors that enabled and challenged quality improvement. Data was collected during two-day site visits, using professional conversations and field notes to elicit the views and experiences of service providers, leaders and educators. In this paper, we look at how the A&R process is experienced by those involved in service provision, with a focus on the factors that enabled and challenged quality improvement. Recognising the interchangeability of enablers and challenges, three broad themes emerged: (i) curriculum knowledge, pedagogical skills and agency; (ii) collaborative leadership and teamwork; and (iii) meaningful engagement in the A&R process, The study found that meaningful engagement in the A&R process informed priorities for ongoing learning and acted as a catalyst for continuous quality improvement. Apprised by stakeholder views and experiences of A&R, we offer a model to foster stakeholder participation in quality assurance matters through affordances of meaningful engagement.